Agronomic Biofortification with Zinc and Iron Improves Yield and Nutrient Content of Bread Wheat - Poudel, Uttam; Sah, Shrawan Kumar (Agronomy Journal of Nepal, 2025)
The rapid progress in developing high yielding wheat varieties during the past also led to significant decline in Zn and Fe content in the grain due to the dilution effect. The Zn and Fe deficiency in cereal grain posed serious health issues in the human being. Zn and Fe content of the grain can be increased either by genetic or agronomic biofortification. A field experiment was carried out to evaluate the effects of agronomic bio-fortification with Zn and Fe on yield, yield attributes, and grain Zn and Fe content of normal and biofortified wheat varieties during winter season of 2021-2022 at Rampur, Chitwan. The experiment was laid out in strip-split plot design with twelve treatments and three replications. The treatments consisted of two varieties of wheat (Zinc Gahun 2 and Vijay) in vertical plots, two iron levels (0 and 10 kg Fe ha-1 soil application) in horizontal plots and three levels of zinc (0, 10, and 20 kg Zn ha-1 soil application) in sub plots. The results revealed that Zinc Gahun 2 produced higher grain yield (4821 kg ha-1), grain zinc content (40.47 mg kg-1) and grain Fe content (39.29 mg kg-1) followed by Vijay (4271 kg ha-1, 31.42 mg kg-1 and 32.61 mg kg-1). Similarly, soil application of Fe at 10 kg ha-1 and Zn at 20 kg ha-1 produced significantly higher grain yield (P< 0.05) (10.04% and 10.11%, respectively) than control. The Zn content increased with increasing Zn levels but decreases with an increase in Fe levels and vice-versa due to their antagonistic effect. Therefore, fertilization of micronutrients (zinc and iron) in both biofortified and non-biofortified wheat varieties is one of the best approaches for farmers to harvest higher yield with enriched Zn and Fe content in their wheat grains.